Fall characteristics among elderly populations in urban and rural areas in Korea. Issue 46 (13th November 2020) - Kim, Myeongkyu; Chang, Misoo; Nam, Eunwoo; Kim, Seul Gi; Cho, Sung-il; Ryu, Dong Hee; Kam, Sin; Choi, Bo Youl; Kim, Mi Jung
Abstract : Abstract: Falling is one of the leading causes of injury among elderly populations. As the population over 65 years old increases, medical costs due to falling will also increase. Urban and rural areas have different fall characteristics, and research into these differences is lacking. A survey was conducted on 2012 people over 60 years old between September 1, 2015, to October 12, 2015. Guro-gu (Seoul), Yeongdeungpo-gu (Seoul), and Jung-gu (Daegu) were classified as urban areas and included 1205 of the study participants. Dalseong-gun (Daegu) and Yangpyeong-gun (Gyeonggi-do) were categorized as rural areas and included 807 participants. The survey included questions about fall history, cause, season and time of recent falls, and external conditions associated with recent falls, like floor or ground materials and shoe types. Rural respondents were older than urban respondents ( P  < .001) but did not differ significantly in gender proportion ( P  = .082). Fall history over the past year was not different between the 2 regions ( P  = .693), but lifetime fall history was greater among rural respondents ( P  < .001). Only 5.1% of all respondents had undergone fall-prevention education. A slippery floor was the most common cause of falls in both regions, but there was a significant difference in pattern of fall causes ( P  < .001). Falls were more frequent in the summer, spring, and the afternoon in urban areas, and in the summer, autumn, and the morning in rural areas. Cement and asphalt were the most common ground materials at the time of falls in both regions, but rural respondents had higher fall rates when walking on soil and when wearing slippers. A fall-prevention program that reflects the characteristics and differences of falls in urban and rural areas should be developed and used to effectively prevent falling among elderly people.